Respuesta :
You can obtain the graph of the function y=-2sinx-1 from the graph of the function y=sinx making such transformations:
1. the multiplication by -2 increases y value twice and then symmetrically reflects the graph y=2sinx about the x-axis;
2. adding -1 to the y=-2sinx you translate the graph 1 unit down.
On the added picture black line is a graph of y=sinx and red line is a graph of y=-2sinx-1.
Check:
1. When x=0, y=-2sin0-1=-1;
2. When [tex]x= \frac{3\pi}{2} [/tex], then [tex]y=-2\sin \frac{3\pi}{2} -1=-2(-1)-1=2-1=1[/tex].
1. the multiplication by -2 increases y value twice and then symmetrically reflects the graph y=2sinx about the x-axis;
2. adding -1 to the y=-2sinx you translate the graph 1 unit down.
On the added picture black line is a graph of y=sinx and red line is a graph of y=-2sinx-1.
Check:
1. When x=0, y=-2sin0-1=-1;
2. When [tex]x= \frac{3\pi}{2} [/tex], then [tex]y=-2\sin \frac{3\pi}{2} -1=-2(-1)-1=2-1=1[/tex].
![Ver imagen frika](https://us-static.z-dn.net/files/d40/d164a03e84fb70c8c9bbb234ac853e11.jpg)
Answer:
You need to include:
The graph of y = –2sin(x) – 1 is the graph of the parent function stretched vertically by a factor of 2, reflected over the x-axis, and shifted 1 unit down.
The maximum of the parent function is 1, the minimum is –1, and the amplitude is 1.
The maximum of y = –2sin(x) – 1 is 1, the minimum is –3, and the amplitude is 2.
Step-by-step explanation:
Correct on edge 2021!